2008
DOI: 10.1080/09064700802400803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fat inclusion at two energy levels on reproductive performance, milk compositions and blood profiles in lactating sows

Abstract: This study was conducted to investigate the effects of dietary fat inclusion to create two energy levels on reproductive performance, milk compositions and blood profiles in lactating sows. Twenty-four multiparous sows were randomly assigned to four treatments according to a 2)2 factorial arrangement. Two energy levels (3365 and 3265 kcal/kg) were created by supplementing different fat levels (high and low). Higher energy level resulted in less (P B0.05) body weight and backfat loss, shorter wean-to-estrus int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
(27 reference statements)
1
14
0
Order By: Relevance
“…() and Park et al. () suggest that isocaloric substitution of the energy source in the diet with a fat source throughout lactation may actually aggravate the negative energy balance by increasing milk output and mobilization of body reserves. Van den Brand et al.…”
Section: Discussionmentioning
confidence: 99%
“…() and Park et al. () suggest that isocaloric substitution of the energy source in the diet with a fat source throughout lactation may actually aggravate the negative energy balance by increasing milk output and mobilization of body reserves. Van den Brand et al.…”
Section: Discussionmentioning
confidence: 99%
“…5 Total MUFA-monounsaturated fatty acids. 6 Total PUFA-polyunsaturated fatty acids. 7 Total n-3 PUFA-omega 3 polyunsaturated fatty acids.…”
Section: Colostrum and Milk Fatty Acidsmentioning
confidence: 99%
“…Increasing the energy density in the lactation diet should help increase energy intake during lactation to better match the demand of the suckling litter whilst minimising catabolism of maternal body reserves. Park et al [6] found that a high energy diet (14.7 MJ/kg DE) in lactation reduced sow body weight and back-fat loss and increased piglet growth to weaning compared to a low energy diet (14.2 MJ/kg DE). Craig et al [7] also reported an increase in litter average daily gain when a high energy diet (15.8 MJ/kg DE) was offered compared to a 'normal' diet (15.2 MJ/kg DE).…”
Section: Introductionmentioning
confidence: 99%
“…However, feed intake decreases as the dietary energy concentration increases [3-5] and as a result, total lysine intake may decline as the energy concentration of the diet increases.…”
Section: Introductionmentioning
confidence: 99%